2015
DOI: 10.1111/cen.12770
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of idiopathic oligozoospermia with recombinant human follicle‐stimulating hormone: a prospective, randomized, double‐blind, placebo‐controlled clinical study in Chinese population

Abstract: The efficacy of FSH treatment was associated with the dose of FSH and duration of treatment, and FSH therapy was more effective in patients with normal level and low level of inhibin B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 23 publications
2
39
0
Order By: Relevance
“…The FSH prescription recorded in this survey reflects the AIFA suggestion, although empirical. It is possible that higher doses/longer durations might be more effective . This is also suggested by a recent meta‐analysis, considering five randomized clinical trials, although based on a low number of patients (372 treated with FSH and 294 non‐treated) .…”
Section: Discussionmentioning
confidence: 95%
“…The FSH prescription recorded in this survey reflects the AIFA suggestion, although empirical. It is possible that higher doses/longer durations might be more effective . This is also suggested by a recent meta‐analysis, considering five randomized clinical trials, although based on a low number of patients (372 treated with FSH and 294 non‐treated) .…”
Section: Discussionmentioning
confidence: 95%
“…Paradisi et al 74,75 and Ding et al 76 have observed in placebo-controlled studies that a high dose of recombinant FSH (300 IU every other day for ≥4-5 months), instead of the standard dose of 75 IU/every other day, significantly increased sperm counts and pregnancy rates.…”
Section: Pharmacological and Genetic Amplification Of Fsh Action: Effmentioning
confidence: 99%
“…Clinical studies in idiopathic infertile men suggested sperm production dependency on the FSH dose [119,120], providing a rationale for optimizing the clinical approaches to the disease, which are currently mostly empirical. Indeed, data from the clinical studies indicated that the use of FSH would not be beneficial in about half of the patients.…”
Section: Fsh Use In Idiopathic Infertility: State-of-the-artmentioning
confidence: 99%